Impact of a fall prevention education program for health and exercise professionals: a randomised controlled trial - Anne Tiedemann; Daina L Sturnieks; Anne-Marie Hill; Lorraine Lovitt; Lindy Clemson; Stephen R Lord; Catherine Sherrington (Sax Institute, 2021)
Objectives and importance of study: Exercise prevents falls among community-dwelling older adults. Therefore, it is crucial that health and exercise professionals have the knowledge and skills to prescribe appropriate fall prevention exercise. This study evaluated the effect of a fall prevention education program, compared with a waitlist control group, on health and exercise professionals' fall prevention knowledge and behaviour, and their confidence to prescribe fall prevention exercises for older people. Study type: Randomised controlled trial. Methods: Participants were 200 health and exercise professionals recruited in New South Wales (NSW), Australia. The intervention group participated in a 1-day face-to-face education workshop on exercise to prevent falls in older age. The waitlist control group received the education intervention after completion of the 3-month follow-up. Primary outcomes were self-reported fall prevention knowledge, and change in prescribing behaviour for fall prevention exercise. Secondary outcomes were: confidence to prescribe fall prevention exercise; proportion of people aged 60 years and older seen in the past month who were prescribed fall prevention exercise; and proportion of fall prevention exercises prescribed in the past month that were evidence based. Data were analysed using analysis of covariance models for continuously scored outcomes and the differences in proportions between groups (relative risk [RR]). Results: The intervention significantly improved knowledge (between-group difference [BGD] 0.27 points out of a possible 6; 95% confidence interval [CI] 0.03, 0.51; p = 0.03), perceived clinical behaviour (RR 5.58; 95% CI 3.25, 9.59; p < 0.001), confidence (BGD 1.02/10 points; 95% CI 0.65, 1.39; p < 0.001) and the proportion of evidence-based exercise prescribed, in both the number of exercises (BGD 0.36; 95% CI 0.03, 0.68; p = 0.03) and percentage of participants who prescribed at least 2 hours/week of fall prevention exercise (RR 1.53; 95% CI 1.08, 2.15; p = 0.015). Conclusion: The education workshop significantly improved participants' knowledge, confidence and behaviour regarding fall prevention exercise prescription.